Gaya Bahasa Satire Elsa Japasal dalam Kanal YouTube Acara Main Hakim Sendiri - Junita, Junita; Fitri, Sakinah; Haliq, Abdul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the satirical language style by Elsa Japasal in the YouTube channel "Main Hakim Sendiri". The style of satirical language is used to express or express criticism or satire of certain events. Elsa Japasal uses a satirical style wrapped in comedy as a form of criticism of social and political issues. In this study, researchers took 10 videos of the YouTube channel of the "Main Hakim Sendiri" event. In this study, the researcher used a qualitative descriptive method. The objectives of this study are: 1) to describe the forms of Elsa Jaarticle's satirical language style that appear in the YouTube channel of the show "Main Hakim Sendiri"; and 2) describe the function of using Elsa Japasal satirical style in conveying criticism in the "Playing Judge Itself" event. In this study, as many as 12 data were obtained in the form of satirical language style sentences consisting of 4 humor satire and 8 ironic satire forms. The results of the study show that there are two main forms of satirical language styles, namely 4 data in the form of humor and 8 data in the form of irony. Both forms function as a means of entertainment as well as a corrective media for the social and political issues raised. These findings show that the style of satirical language plays an important role in building people's critical awareness of social reality through digital media.